The Subject of This Study is the Multiphase Flow of a Compressible Liquid in a Porous Medium, Specifically Focusing on Classification - Bustanov A. Khudaykul (International Journal on Human-Computing Studies, 2024)
Modeling the flow of two-phase compressible fluids through porous media is very pertinent to a broad spectrum of physical and technical applications. The study focuses on reservoir modeling and oil and gas production, which require the use of advanced numerical methods to ensure efficiency. The objective is to achieve a numerical solution to this model by integrating finite element and finite volume approaches. This involves generating velocity values at the boundary of the finite volume grid cells based on point pressure values at KE nodes.